An energy-aware distributed algorithm for virtual backbone in wireless sensor network with different transmission range - Fakhar, Mohammad Amin Ebrahimzadeh; Tabbakh, Seyed Reza Kamel (Ciência e Natura, 2015)
Since there is no fixed infrastructure or centralized management in Wireless Sensor Networks (WSNs), a Connected Dominating Set(CDS) has been proposed as a virtual backbone is efficient. A virtual backbone plays a major role in routing, broadcasting, coverage andactivity scheduling. Wireless sensor networks to form a CDS usually by UDG (Unit Disk Graph) models that are used in this model, allnodes have the same message, but this article UDG model instead of a version that is closer to reality called DGB (Disk Graph withBidirectional links) is used in which nodes can adopt different transmission intervals. In many applications, to reduce overhead, increasenetwork lifetime, and so on, to find the MCDS (minimum connected dominating set) is desirable, but the point is that MCDS UDG modelsand DGB, the problem is NP-hard. In addition to the analysis of algorithms, the new algorithm will provide and the efficiency of thealgorithm, especially in terms of energy consumption, through theoretical analysis and simulation algorithms are available to be checked out.